"The major prize": apartheid South Africa's accession to the Treaty on the Non-Proliferation of Nuclear Weapons, 1988–91. Issue 5 (2nd September 2019) - Möser, Robin
ABSTRACT: This article focuses on the final years of South Africa's nuclear-weapon program, particularly on the decision-making process leading up to the signature of the 1968 Treaty on the Non-Proliferation of Nuclear Weapons (NPT) by the South African government in 1991. In August 1988, after two decades of defiance, negotiations between the apartheid government and the NPT depository powers (the United Kingdom, the United States, and the Soviet Union) ensued at the International Atomic Energy Agency (IAEA) in Vienna. Despite South Africa being the only state to give up its indigenously developed nuclear weapons and subsequently join the nonproliferation regime, little is known about how the national position on NPT accession and IAEA safeguards evolved. Research carried out in multiple archives using hitherto untapped primary sources and interviews with key actors from several countries show how domestic and regional political dynamics influenced Pretoria's position on entering the nonproliferation regime. In the process, the F.W. de Klerk government managed to skillfully exploit international proliferation fears to advance its own agenda, thereby connecting South African NPT accession with that of the neighboring Frontline States coalition of Angola, Mozambique, Tanzania, Zambia, and Zimbabwe.